The Effects of Inattentiveness and Hyperactivity on Posttraumatic Stress Symptoms: Does a Diagnosis of Posttraumatic Stress Disorder Matter?. Issue 9 (July 2020) - Adams, Zachary; Adams, Thomas; Stauffacher, Kirstin; Mandel, Howard; Wang, Zhewu
Objective: To address the nature of associations between ADHD symptoms and posttraumatic stress disorder (PTSD) psychopathology in adult military veterans.Method: Ninety-five combat veterans, with PTSD ( n = 63) and without PTSD ( n = 32), were recruited for this study. PTSD was assessed with the Clinician-Administered PTSD Scale (CAPS) and ADHD was assessed with Connors' Adult ADHD Rating Scale−Self-Report: Short Version (CAARS-S:S).Results: PTSD participants endorsed greater hyperactivity or restlessness, inattention or memory problems, and impulsivity or emotional lability scores than participants without PTSD. Among PTSD participants, inattention or memory problems and impulsivity or emotional lability were significant predictors of total PTSD symptoms, but only inattention or memory problems significantly predicted PTSD symptoms when other ADHD symptom clusters were considered simultaneously.Conclusion: Our data suggest that inattention may serve as a risk factor for posttraumatic stress symptoms following combat exposure.